RENAL INVOLVEMENT IN LEPTOSPIROSIS - Galya I. Gancheva (Peytchinski Publishing, 2012)
Renal involvement is a common feature of leptospirosis. It is variable from mild to severe acute renal failure. Materials and methods: We performed analysis of 100 consecutive leptospirosis cases treated in Clinic of Infectious Diseases at University Hospital - Pleven (1976-2012) (90 male, age 37±18 years, lethal outcome in 13%), followed by comparative analysis of group with renal involvement (n1=59) versus group without renal involvement (controls: n2=41). Results: Fever (100%), hepatomegaly (92%), myalgia (86%), nausea and vomiting (84%), splenomegaly (74%), oliguria (69%), headache (67%), jaundice (63%), hypotension (49%), abdominal pain (41%), and hemorrhagic diathesis (37%) were the characteristic manifestations and had had a significantly higher prevalence in the group with renal involvement. Blood urea nitrogen (mean 27.9±16.9 mmol/L) and serum creatinine (mean 349.9±190.1 µmol/L) were the main laboratory parameters that expressed renal dysfunction in this group. Dialysis was performed in twelve severe cases. Conclusion: Leptospirosis with acute renal failure is a severe disease and requires early diagnosis and prompt treatment.